DESCRIPTION OF FOLKLORE, EPICS - Mamatkhalilova, Dinora Mukhtorovna (Educational Research in Universal Sciences, 2024)
This article discusses the national epics containing the national customs and traditions of the Uzbek people and their classification, their role and importance in studying the culture and past of our people.